(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
In the current digital era, technological developments are very rapid, especially in the form of digital media that are widely used by the community, especially in the field of education. The purpose of this article is to analyze the effectiveness of using Google Sites in increasing students’ interest in learning mathematics. Google Sites is an interactive and innovative website platform which can be used as an interesting learning medium in mathematics subjects. By combining various media such as text, video, audio, and games. Google Sites can display content that helps students understand the material. In addition, easy access through various devices such as smartphones and Windows computers makes this platform flexible to use. Data analysis in this study uses a literature study method based on several previous journals. Previous studies have shown that the application of Google Sites in mathematics learning can have a positive impact, especially in increasing students’ interest in learning. Thus, the use of learning media using Google Sites is expected to be able to support the implementation of the mathematics learning process and can be used as a source of independent learning by students.